Kemampuan Berbicara Efektif dengan Teknik Bercerita siswa kelas VIII SMP Metta Maitreya Kecamatan Marpoyan Damai Pekanbaru Tahun Ajaran 2020/2021 - Apik, Apik; Supriyadi (UIR PRESS, 2021)
The purpose of this study is to describe, analyze, interpret and conclude effective speaking skills with storytelling techniques for Class VIII students of SMP Metta Maitreya, Marpoyan Damai District, Pekanbaru in the academic year 2020/2021 systematically so that they can find out the actual objective picture. The theory used in this study is the theory of Hartono 2007. The sample in this study was 62 students. This research method uses a quantitative descriptive method. So overall the ability to speak effectively with storytelling techniques for Class VIII Middle School students Metta Maitreya, Marpoyan Damai District, Pekanbaru in the 2020/2021 school year is categorized as good with an average score of 76.51. The average value assessed from the aspect of reasoning is classified as good, namely 77.02 from 62 students. The average value assessed from the intonation aspect in the good category is 76.61 out of 62 students. So overall the ability to speak effectively with storytelling techniques for Class VIII Middle School students of Metta Maitreya, Marpoyan Damai District, Pekanbaru in the 2020/2021 school year is categorized as good with an average score of 76.51.